The Effect of Financial Distress and Auditor Switching on Audit Report Lag - Antony, Priska Cecilia; Jantong, Alfonsus; Kampo, Kunradus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
The purpose of this study is to investigate the effect of financial distress and auditor switching on audit report lag. This study uses a purposive sampling method with secondary data sources, namely the financial and annual reports of manufacturing companies on the Indonesia Stock Exchange (IDX) in 2021-2023. The research method used is a quantitative approach with multiple linear regression analysis techniques. The total sample that meets the criteria is 101 companies. The results of this study indicate that financial distress has a negative and significant effect on audit report lag, and auditor switching has a positive and significant effect on audit report lag.